Effects of Exogenous Insulin Therapy on Thyroid Nodule Size in Patients with Type 2 Diabetes Mellitus - Samer El-Kaissi; Badurudeen Mahmood Buhary; Suphia Sherbeeni (Open Journal of Thyroid Research - Peertechz Publications, 2017)
Objectives: Recent evidence suggests that insulin resistance and endogenous hyperinsulinaemia are related to thyroid nodule growth and development, but the effect of exogenous insulin therapy on thyroid nodules is unknown. The objectives of this study are to investigate the effects of exogenous insulin on thyroid nodule size in diabetic patients. Methods: retrospective analysis of patients with nodular thyroid disease and type 2 diabetes mellitus receiving metformin alone or insulin-and-metformin. Thyroid ultrasonography was used to monitor changes in nodule size: ≥2 mm and ≥20% being statistically significant. Results: 34 insulin-treated (73 nodules) and 53 metformin-only (135 nodules) patients were followed for 5.9-67.9 months (mean 24.5±1.8). Nodule size ranged from 0.17-5.25 cm (mean 1.29±0.08). There were no signifi cant differences in serum TSH, free-T4 or Vitamin D between the two groups, but haemoglobin A1C was higher in insulin-treated patients at baseline and during follow-up (8.75±0.12% vs. 6.48±0.08%; P-value <0.001). In insulin-treated patients, the number of nodules with no change, increase or decrease in size were 49/73 (67.12%), 13/73 (17.81%) and 11/73 (15.07%) at the end of follow-up. The respective number of nodules in the metformin-only group were 105/135 (77.78%), 20/135 (14.81%) and 10/135 (7.41%). Chi-square test for type of treatment and changes in nodule size was not significant (P-value 0.15).